Weavers: A Community-driven Approach to Enabling Sustainable EdTech Transformations in South Korea - Lim, Sung Hee; Choi, Baekhyeon; Lee, Kyungmee (Proceedings of the International Conference on Networked Learning, 2026)
This experimental design study departs from a problematization of South Korea’s recent attempt to introduce AI Digital Textbooks (AIDT) as part of its national EdTech reform project, highlighting the limitations of a top-down, technology-centric policy approach. Despite the government’s optimistic vision of achieving “personalized education for all,” the initiative rapidly declined following widespread dissatisfaction with its limited functionality, lack of pedagogical integration, and the absence of teacher agency in its implementation. Drawing from this arguably unsuccessful case, the study applies the expanded design framework of Transformative Networked Learning (TNL) (Lee & Bligh, 2023) to propose an alternative, bottom-up model for sustainable EdTech transformations in Korean education settings and beyond. The TNL framework reorients Networked Learning (NL) toward its critical pedagogical roots, emphasizing learning as a process of ontological and axiological transformation. Learning occurs through the dynamic interplay of three communities: an internal community of collaborative reflection, an external community of real-world praxis, and a society as a community of bro ader structural transformation. In this study, these communities are instantiated through the “Weavers” project, which brings together teachers, EdTech company representatives, and educational researchers to co-design and enact contextually relevant, critically informed lesson plans. Fifteen in-service teachers (who are also doing graduate studies) and fifteen EdTech representatives participated in a series of collaborative design workshops—both online and in-person—supported by researchers from Seoul National University. Within this internal community, participants co-developed a critical understanding of EdTech adoption and collaboratively designed technology-integrated lessons. The teachers will next implement these lessons in their classrooms (external community), documenting their practices through multimodal data collection, including classroom recordings and reflective interviews. Insights gained will then circulate back into the internal community for collective analysis, feeding forward into broader society as community discussions among policymakers, administrators, and the public. By embedding critical inquiry and reflective practice within the design and enactment of EdTech use, this study positions teachers not as passive recipients of policy but as active weavers of EdTech transformation. The anticipated outcomes highlight the potential of TNL as a framework for reconfiguring educational ecosystems from within, demonstrating that sustainable innovation in education arises not from technological mandates but from nurturing organic, networked collaborations among students, teachers, researchers, developers, and technologies. Ultimately, the study offers both theoretical and practical contributions toward cultivating a democratic, teacher-driven model of digital educational reform.